Christian Unity in Stone-Campbell Movement - Douglas A. Foster (Kairos (English Ed.), 2008)
Author offers review of the backgrounds to Stone-Campbell concepts of Christian unity, insides on the early unity impulse in the Stone-Campbell Movement, as well as the development of the idea of unity in the Post-Bellum Period. A valuable explanation is offered on the twentieth-century understandings of unity in the Three Streams, and on the efforts at internal unity in the Stone-Campbell Movement.